2018
DOI: 10.1002/ldr.3021
|View full text |Cite
|
Sign up to set email alerts
|

Recurring surface fires cause soil degradation of forest land: A simulation experiment with the EFIMOD model

Abstract: Renewal of pine forests is ecologically dependent on fires, but if fires become too frequent, they can disrupt the equilibrium and sustainability of these ecosystems. Field studies of the effects of fire are challenging because of the heterogeneity of forest ecosystems and because of the heterogeneous effect of fire on recovery of vegetation. As an alternative to complex field studies, mathematical models can be used as a tool to assess the complex dynamics of natural ecosystems as they recover after fire. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The highest values of phosphorus and potassium in burnt abandoned arable can be explained by high residual levels of P and K in the former arable soils (Gough and Marrs 1990;Marrs et al 1991) and high rates of element cycling in communities supported by periodical fires (Rabotnov 1982;Bleken et al 1997). Decrease in soil carbon and nitrogen values is reported with increase of fire frequency in savanna and broad-leaved forests (Pellegrini et al 2018) and in Scots pine forests in the hemiboreal and nemoral regions of European Russia (Nadporozhskaya et al 2018). Reich et al (2001) also revealed that carbon and nitrogen cycling is tightly coupled across fire frequency and vegetation type gradients: the combination of low fire frequency and high tree dominance leads to high rates of N cycling, while the opposite, high fire frequency and high grass dominance, leads to low rates of N cycling.…”
Section: Discussionmentioning
confidence: 94%
“…The highest values of phosphorus and potassium in burnt abandoned arable can be explained by high residual levels of P and K in the former arable soils (Gough and Marrs 1990;Marrs et al 1991) and high rates of element cycling in communities supported by periodical fires (Rabotnov 1982;Bleken et al 1997). Decrease in soil carbon and nitrogen values is reported with increase of fire frequency in savanna and broad-leaved forests (Pellegrini et al 2018) and in Scots pine forests in the hemiboreal and nemoral regions of European Russia (Nadporozhskaya et al 2018). Reich et al (2001) also revealed that carbon and nitrogen cycling is tightly coupled across fire frequency and vegetation type gradients: the combination of low fire frequency and high tree dominance leads to high rates of N cycling, while the opposite, high fire frequency and high grass dominance, leads to low rates of N cycling.…”
Section: Discussionmentioning
confidence: 94%
“…Fires now occur every decade or even annually, often escalating in size and severity (Cochrane, 2003;Flannigan et al, 2009;Uhl & Kauffman, 1990). Fires are associated with biodiversity changes (Kelly et al, 2017;Kelly et al, 2020), soil degradation (Nadporozhskaya et al, 2018), erosion (Girona-García et al, 2024), impacts on freshwater ecosystems (Vaz et al, 2014(Vaz et al, , 2021, diminished water retention (Sansevero et al, 2017;Schmerbeck & Fiener, 2015), and landscape dynamics alterations (Silva et al, 2011;Moreira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Russia's forests serve as carbon sinks from the atmosphere, providing 34 billion tonnes of carbon out of 500 billion tonnes of global terrestrial biomass, with coniferous forests accounting for over 25 billion tonnes [1]. Human influence has led to an increase in the frequency and extent of wildfires, which negatively impact stand productivity [2] and increase the uptake of PyrCo into the soil. Therefore, there is presently a scientific emphasis on reforestation and improving forest productivity.…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of research on the thin pyrogenic layers that lie beneath the forest floor on the mineral soil surface, comprising a mixture of charcoal, detritus, humus, and mineral particles. In scientific literature, the terms 'litter' and 'forest floor' both refer to a surface organic horizon measuring up to 10 cm, but neither has been sufficiently studied [1,2,8]. While the three terms have been used interchangeably, this paper deems 'forest floor' as the more accurate option.…”
Section: Introductionmentioning
confidence: 99%